Lithium ion battery electrolyte and application thereof
By using a specific electrolyte in lithium-ion batteries, the problem of deterioration in cycle life of high-energy-density batteries is solved, and higher fast charging and high-temperature performance are achieved.
Patent Information
- Application Number
- CN202411942025.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-26
AI Technical Summary
When lithium-ion batteries use high-energy density positive and negative electrode materials, their cycle life has deteriorated significantly, hindering their large-scale commercial application.
A lithium-ion battery electrolyte is provided, which contains nonaqueous solvents (such as perfluorohexanone and methyl ethyl carbonate), lithium salts and additives (such as triallyl isocyanurate), which improves the electrochemical stability and kinetic properties of the electrolyte by optimizing the solvent ratio and additive content.
This electrolyte effectively improves the fast charging performance, cycle life and high temperature performance of lithium-ion batteries, and is suitable for high energy density lithium-ion batteries.
Smart Images

Figure BDA0005212845620000151
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of power batteries, and in particular to a lithium-ion battery electrolyte and applications thereof. Background Art
[0002] At present, lithium-ion batteries are developing rapidly in the fields of electric vehicles and large-scale energy storage, occupying a large market share. With the widespread application of lithium-ion batteries, consumers also have higher demands for the energy density and cycle life of lithium-ion batteries. This is achieved by using positive and negative electrode materials with higher specific capacity, such as high nickel positive electrode materials or silicon negative electrode materials, but the application of these materials often leads to a significant deterioration in the cycle life of the battery, hindering its large-scale commercial application. Summary of the invention
[0003] The present invention proposes a lithium ion battery electrolyte and its application. The electrolyte obtained by the lithium ion battery electrolyte and its application provided by the present invention can be applied to high energy density lithium ion batteries, improve the fast charging performance of lithium ion batteries, improve the cycle performance of lithium ion batteries, and improve the high temperature performance of batteries.
[0004] In order to solve the above technical problems, the present invention provides a lithium ion battery electrolyte, comprising at least the following components:
[0005] A non-aqueous solvent, the non-aqueous solvent comprising a first solvent and a second solvent, the first solvent being selected from at least one of perfluorohexanone, decafluoropentane or 2,2-bis(trifluoromethyl)-1,3-dioxolane;
[0006] lithium salts; and
[0007] The additives include a first additive including triallyl isocyanurate.
[0008] In one embodiment of the present invention, the content of the first solvent in the electrolyte is 5 wt % to 40 wt %.
[0009] In one embodiment of the present invention, the content of the first additive in the electrolyte is 0.01 wt % to 1 wt %.
[0010] In one embodiment of the present invention, the second solvent is selected from at least one of ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, propylene carbonate or ethylene carbonate.
[0011] In one embodiment of the present invention, the second solvent is selected from ethyl methyl carbonate, and the mass ratio of the first solvent to the second solvent is 1:1.83 to 1.25:1.
[0012] In one embodiment of the present invention, the lithium salt is selected from at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethylsulfonyl imide), lithium dioxalatoborate, lithium difluorobis(oxalatophosphate), lithium difluorooxalatoborate or lithium trifluoromethylsulfonate, and the content of the lithium salt in the electrolyte is 10wt% to 20wt%.
[0013] In one embodiment of the present invention, the additive further includes a second additive, the second additive includes lithium difluorophosphate, and the content of the second additive in the electrolyte is 0.05wt% to 2.5wt%.
[0014] In one embodiment of the present invention, the mass ratio of the first additive to the second additive is (0.3-1):1.
[0015] In one embodiment of the present invention, the additive further includes a third additive, the third additive is selected from at least one of tri(trimethylsilyl)borate, tripropynyl phosphate, ethylene sulfite or lithium tetrafluoroborate, and the content of the three additives in the electrolyte is 0.01wt% to 1wt%.
[0016] The present invention also provides a lithium ion battery, comprising:
[0017] Positive electrode;
[0018] A negative electrode plate, the negative electrode plate comprising a negative electrode active material, the negative electrode active material comprising a combination of at least one of soft carbon, hard carbon, artificial graphite, natural graphite, silicon or lithium titanate and a silicon-carbon compound, wherein the content of the silicon-carbon compound in the negative electrode active material is 10wt% to 40wt%;
[0019] A diaphragm, disposed between the positive electrode sheet and the negative electrode sheet;
[0020] The electrolyte is selected from the lithium-ion battery electrolyte described above.
[0021] In summary, the present invention proposes a lithium-ion battery electrolyte and its application. The first solvent and the second solvent are used together to make the electrolyte have good electrochemical stability and good kinetic performance at the same time, which can effectively improve the fast charging performance of the battery and improve the cycle life of the lithium-ion battery. By adding the first additive, the reaction rate of the salt anion at the interface can be effectively slowed down, thereby alleviating the problem of excessive local temperature, and the high temperature performance of the lithium-ion battery is further improved. The obtained electrolyte can be applied to high-energy-density lithium-ion batteries, improve the fast charging performance of lithium-ion batteries, improve the cycle performance of lithium-ion batteries, and improve the high temperature performance of batteries. DETAILED DESCRIPTION
[0022] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0023] It should be understood that the present invention can be implemented in different forms and should not be interpreted as limited to the embodiments set forth herein. On the contrary, these embodiments are provided to make the disclosure thorough and complete and to fully convey the scope of the present invention to those skilled in the art.
[0024] The technical scheme of the present invention is further described in detail below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0025] The present invention provides a lithium ion battery electrolyte, comprising at least a non-aqueous solvent, a lithium salt and an additive, wherein the non-aqueous solvent comprises a first solvent and a second solvent, the first solvent is selected from at least one of perfluorohexanone, decafluoropentane or 2,2-bis(trifluoromethyl)-1,3-dioxolane, and the first additive comprises triallyl isocyanurate (TAIC), and the structural formula of triallyl isocyanurate is The lithium-ion battery electrolyte provided by the present invention can be applied to lithium-ion batteries with high energy density, improve the fast charging performance of lithium-ion batteries, improve the cycle performance of lithium-ion batteries, and improve the high-temperature performance of batteries.
[0026] In one embodiment of the present invention, the second solvent is selected from at least one of ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), propylene carbonate (PC) or ethylene carbonate (EC). In this embodiment, the second solvent is selected from ethyl methyl carbonate, for example. Among them, the first solvent can hardly dissolve lithium salts, and the coordination effect with lithium ions is weak. When the first solvent is mixed with the second solvent, the coordination probability of lithium ions and anions in the formed electrolyte increases, and the migration rate of lithium ions increases, which can effectively improve the fast charging performance of the battery. In the electrolyte, the salt anions at the electrode / electrolyte interface will preferentially and more decompose into inorganic compounds such as lithium fluoride (LiF), and the reaction activity of the solvent molecules at the interface is reduced, thereby enhancing the redox stability of the electrolyte and improving the cycle life of the lithium ion battery using the electrolyte.
[0027] In one embodiment of the present invention, the content of the first solvent in the electrolyte is 5wt% to 40wt%, for example 20wt% to 35wt%, and the mass ratio of the first solvent to the second solvent is 1:1.83 to 1.25:1. When the mass ratio of the first solvent to the second solvent is within this range, the electrolyte will have both good electrochemical stability and good kinetic properties. If its mass ratio is less than 1:1.83, the content of the first solvent is too much, the lithium salt cannot be well dissolved and dissociated, the kinetic properties of the electrolyte are greatly affected, and the battery cannot play a good capacity. If its mass ratio is greater than 1.25:1, the content of the first solvent is too little, the solvation structure of the electrolyte cannot be effectively regulated, the electrochemical stability of the electrolyte cannot be improved, and the cycle life of the battery is affected. Therefore, the mass ratio of the first solvent to the second solvent is controlled to ensure the full dissolution of the lithium salt and improve the stability of the electrolyte.
[0028] In one embodiment of the present invention, the first additive acts as a film-forming additive and can be preferentially decomposed into a nitrogen-containing polymer in the electrolyte, thereby enhancing the flexibility of the interfacial phase and effectively slowing down the reaction rate of the salt anions at the interface, thereby alleviating the problem of excessive local temperature, and further improving the high-temperature performance of the lithium-ion battery.
[0029] In one embodiment of the present invention, the content of the first additive in the electrolyte is 0.01wt% to 1wt%, and for example, 0.2wt% to 0.5wt%. If the content of the first additive is too low, the decomposition rate of the salt anions cannot be effectively slowed down, the interface phase is unstable, and the cycle performance of the battery is affected. If the content of the first additive is too high, the organic content in the interface phase is too high, the impedance increases, thereby affecting the dynamics of the battery and affecting the fast charging performance. Therefore, the content of the first additive is controlled to improve the cycle performance and fast charging performance of the lithium-ion battery.
[0030] In one embodiment of the present invention, the additive further includes a second additive, and the second additive includes lithium difluorophosphate (LiPO 2 F 2 ), and the content of the second additive in the electrolyte is, for example, 0.05wt% to 2.5wt%. The second additive, as a film-forming additive, synergizes with the first additive to further improve the quality of the formed interface phase. In a specific embodiment of the present invention, the mass ratio of the first additive to the second additive is, for example, (0.3-1):1. If the mass ratio of the first additive to the second additive is lower than a specific ratio range, the viscosity of the electrolyte decreases due to the limited solubility of the lithium salt, which in turn leads to an increase in impedance. If the mass ratio of the first additive to the second additive exceeds this ratio range, the proportion of inorganic components in the interface phase will decrease, causing the cycle performance of the battery to decline.
[0031] In one embodiment of the present invention, the additive further comprises a third additive, the third additive is selected from at least one of tris(trimethylsilyl)borate, tripropynyl phosphate, ethylene sulfite or lithium tetrafluoroborate, and the content of the three additives in the electrolyte is 0.01wt% to 1wt%. The third additive can cooperate with the first additive and the second additive to further improve the integrity and compactness of the interface phase, and improve the cycle performance and safety performance of the lithium-ion battery.
[0032] In one embodiment of the present invention, the lithium salt is selected from lithium hexafluorophosphate (LiPF 6 ), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(oxalatoborate) (LiBOB), lithium difluorobis(oxalatophosphate) (LiDFOP), lithium difluorooxalatoborate (LiODFB), or lithium trifluoromethanesulfonate (CF 3 SO 3 The content of the lithium salt in the electrolyte is, for example, 10 wt % to 20 wt %.
[0033] In one embodiment of the present invention, when preparing the electrolyte, in a glove box with an inert gas atmosphere such as argon gas with a moisture content and an oxygen content less than or equal to 0.1 ppm, the non-aqueous solvent is mixed uniformly according to the mass ratio, and the fully dried lithium salt is added to the non-aqueous solvent, and an additive is added to prepare a lithium ion battery electrolyte. The content described in this application is the weight percentage calculated based on the total weight of the electrolyte.
[0034] The present invention proposes a lithium-ion battery, which includes a shell and a bare cell arranged in the shell, and the bare cell includes a positive electrode sheet, a separator and a negative electrode sheet. The separator is placed between the positive / negative electrode sheets to prevent the positive / negative electrode from short-circuiting, so that lithium ions can pass through. The positive electrode sheet, the separator and the negative electrode sheet are stacked in sequence to ensure that a separator is provided between any positive electrode sheet and any negative electrode sheet, and a multi-layer laminate is obtained by winding or folding, and is loaded into a battery shell as a bare cell. Finally, an electrolyte is injected into the shell once or multiple times so that the bare cell is completely immersed in the electrolyte. The electrolyte is, for example, selected from the above-mentioned electrolytes, and plays a role in conducting ions between the positive and negative electrode sheets. In one embodiment of the present invention, the lithium-ion battery is, for example, a secondary battery, and the secondary battery is, for example, a soft-pack battery, a square shell battery or a cylindrical battery, etc. The present invention does not specifically limit the type of lithium-ion battery.
[0035] In one embodiment of the present invention, the positive electrode sheet includes a positive current collector and a positive active layer coated on at least one surface of the positive current collector. The positive current collector is, for example, a foil formed by surface treatment of nickel, titanium, aluminum, silver, stainless steel or carbon. In addition to the foil, the positive current collector can also be used in any one or more combinations of various forms such as film, mesh, porous, foam or non-woven fabric. The thickness of the positive current collector is, for example, 8μm to 15μm. In this embodiment, the positive current collector is, for example, aluminum foil, and the thickness of the aluminum foil is, for example, 13μm.
[0036] In one embodiment of the present invention, the positive electrode active layer includes a positive electrode active material, a binder and a conductive agent. Among them, the positive electrode active material includes, for example, lithium nickel manganese oxide, lithium iron phosphate, lithium iron manganese phosphate, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminum oxide, etc., any one or a combination of at least two, so as to improve the energy density of the lithium ion battery. The binder is, for example, selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer (ETFE), vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer (TFE-HFP-VDF) or tetrafluoroethylene-hexafluoropropylene copolymer (FEP). The conductive agent is, for example, selected from any one or more of conductive carbon black (Super P), acetylene black or Ketjen black. The mass ratio of the positive electrode active material, the conductive agent, and the binder in the positive electrode active layer is, for example, (90 to 97):(1 to 5):(2 to 5).
[0037] In one embodiment of the present invention, the positive electrode active material is, for example, LiNi 0.9 Mn 0.05 Co 0.05 O 2 , the conductive agent is selected from acetylene black, the binder is selected from polyvinylidene fluoride, the positive electrode active material, the conductive agent and the binder are mixed in a mass ratio of 95:3:2, and then an organic solvent is added, and the mixture is stirred and mixed to obtain a positive electrode slurry. Among them, the organic solvent is selected from N-methylpyrrolidone (NMP), for example. The positive electrode slurry is evenly coated on an aluminum foil, and then transferred to an oven for drying after drying at room temperature, and the positive electrode sheet is obtained through cold pressing and other processes. The present application does not limit the preparation method of the positive electrode sheet. In other embodiments, the positive electrode sheet can also be obtained by any other method of forming the positive electrode sheet.
[0038] In one embodiment of the present invention, the negative electrode plate includes, for example, a negative electrode current collector and a negative electrode active layer coated on at least one surface of the negative electrode current collector. The negative electrode current collector is, for example, selected from a copper foil current collector, a composite copper foil current collector, a carbon current collector, a foam copper current collector, or a stainless steel current collector, and the thickness of the negative electrode current collector is, for example, 8 μm to 15 μm. In this embodiment, the negative electrode current collector is, for example, copper foil, and the thickness of the copper foil is, for example, 13 μm.
[0039] In one embodiment of the present invention, the negative electrode active layer includes a negative electrode active material, a conductive agent, a binder and a thickener. The negative electrode active material includes, for example, a combination of at least one of soft carbon, hard carbon, artificial graphite, natural graphite, silicon or lithium titanate and a silicon-carbon compound, wherein the content of the silicon-carbon compound in the negative electrode active material is 10wt% to 40wt%, so as to improve the energy density of the lithium-ion battery. The binder is, for example, selected from at least one of styrene butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylic amide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) or carboxymethyl chitosan (CMCS). The thickener is, for example, carboxymethyl cellulose sodium (CMC-Na), and the conductive agent is, for example, selected from any one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene or carbon nanofibers. The mass ratio of the negative electrode active material, the conductive agent, the binder and the thickener in the negative electrode active layer is, for example, (94-97):(1-2):(1-2):(1-2).
[0040] In one embodiment of the present invention, the negative electrode active material is selected from graphite and silicon-carbon compounds, and the mass ratio of silicon-carbon compounds to graphite is, for example, 3:7. By mixing graphite and silicon-carbon compounds, the energy density of lithium-ion batteries can be improved, the specific energy can be improved, and the cycle performance and fast charging performance can be improved. The conductive agent is selected from acetylene black, the thickener is selected from sodium carboxymethyl cellulose, and the binder is selected from styrene-butadiene rubber. In one embodiment of the present invention, the negative electrode active material, the conductive agent, the binder and the thickener are mixed, for example, in a mass ratio of 96:2:1:1, deionized water is added, and the mixture is stirred and mixed to obtain a negative electrode slurry. The negative electrode slurry is coated on a copper foil, and then transferred to an oven for drying after drying at room temperature, and a negative electrode sheet is obtained after cold pressing and other processes. In other embodiments, the negative electrode sheet can also be obtained by any other method of forming a negative electrode sheet.
[0041] In one embodiment of the present invention, the diaphragm is, for example, a polyethylene film (PE), a polypropylene film (PP), a glass fiber film or a composite film, and the thickness of the diaphragm is, for example, 9 μm to 15 μm. In one embodiment of the present invention, the diaphragm is, for example, a polyethylene of 8 μm to 10 μm as a base film, and a nano-aluminum oxide coating with a thickness of 2 μm to 4 μm is coated on at least one side of the base film.
[0042] In one embodiment of the present invention, the positive electrode sheet, the separator, and the negative electrode sheet are placed in sequence, so that the separator is located between the positive electrode sheet and the negative electrode sheet to play an isolating role, and a bare cell is obtained by winding or stacking. The bare cell is placed in a shell, baked at 80°C to remove water, and then sealed after injecting electrolyte. After that, a lithium-ion battery is obtained through processes such as standing, hot and cold pressing, formation, clamping, and capacity division.
[0043] Hereinafter, the present invention will be explained in more detail by citing examples, which should not be construed as limiting. Appropriate modifications may be made within the scope consistent with the gist of the present invention, all of which fall within the technical scope of the present invention.
[0044] Example 1
[0045] Preparation of electrolyte: In an argon glove box with an oxygen content of 0.1 ppm and a water content of 0.1 ppm, perfluorohexanone and EMC were mixed in a mass ratio of 1:1 to obtain a mixed solvent, and lithium hexafluorophosphate and TAIC were added to the mixed solvent. In the electrolyte, the content of lithium hexafluorophosphate was 15 wt%, and the content of TAIC was 0.3 wt%.
[0046] Preparation of positive electrode sheet: After lithium iron phosphate, acetylene black and polyvinylidene fluoride are mixed in a mass ratio of 95:3:2, NMP is added, and the mixture is stirred thoroughly to obtain positive electrode slurry. The positive electrode slurry is evenly coated on aluminum foil, and then transferred to an oven for drying after drying at room temperature, and the positive electrode sheet is obtained through a cold pressing process.
[0047] Preparation of negative electrode sheet: The negative electrode active materials are graphite and silicon-carbon compound, and the mass ratio of silicon-carbon compound to graphite is 3:7. The negative electrode active material, acetylene black, styrene-butadiene rubber and sodium carboxymethyl cellulose are mixed in a mass ratio of 96:2:1:1, deionized water is added, and the mixture is fully stirred to obtain negative electrode slurry. The negative electrode slurry is coated on copper foil, and then dried at room temperature and transferred to an oven for drying. After a cold pressing process, a negative electrode sheet is obtained.
[0048] Selection of diaphragm: A polyethylene with a thickness of 9 μm was used as a base film, and a nano-aluminum oxide coating with a thickness of 3 μm was coated on both sides of the base film to obtain a diaphragm.
[0049] Preparation of battery: stack the positive electrode sheet, separator and negative electrode sheet in order, so that the separator is in the middle of the positive electrode sheet and the negative electrode sheet to play an isolating role, and stack the sheets to obtain a bare cell. Then put the bare cell into an aluminum plastic film, bake it at 80℃ to remove water, inject electrolyte and seal it, and then go through the steps of standing, hot and cold pressing, formation, clamping and capacity division to obtain a soft-pack lithium-ion secondary battery.
[0050] Example 2
[0051] In the electrolyte, the mass ratio of perfluorohexanone to EMC is 2.4:1, and the other steps are consistent with Example 1.
[0052] Example 3
[0053] In the electrolyte, the mass ratio of perfluorohexanone to EMC is 1.83:1, and the other steps are consistent with Example 1.
[0054] Example 4
[0055] In the electrolyte, the mass ratio of perfluorohexanone to EMC is 1.25:1, and the other steps are consistent with Example 1.
[0056] Example 5
[0057] In the electrolyte, the mass ratio of perfluorohexanone to EMC is 1:1.25, and the other steps are consistent with Example 1.
[0058] Example 6
[0059] In the electrolyte, the mass ratio of perfluorohexanone to EMC is 1:1.83, and the other steps are consistent with Example 1.
[0060] Example 7
[0061] In the electrolyte, the mass ratio of perfluorohexanone to EMC is 1:2.4, and the other steps are consistent with Example 1.
[0062] Example 8
[0063] In the electrolyte, perfluorohexanone was replaced with decafluoropentane, and the other steps were consistent with Example 1.
[0064] Example 9
[0065] In the electrolyte, perfluorohexanone was replaced with 2,2-bis(trifluoromethyl)-1,3-dioxolane, and the other steps were consistent with Example 1.
[0066] Example 10
[0067] In the electrolyte, EMC was replaced by dimethyl carbonate, and the other steps were the same as those in Example 1.
[0068] Embodiment 11
[0069] In the electrolyte, EMC was replaced by diethyl carbonate, and the other steps were the same as those in Example 1.
[0070] Example 12
[0071] In the electrolyte, the content of TAIC is 0.1 wt %, and the other steps are consistent with Example 1.
[0072] Embodiment 13
[0073] In the electrolyte, the content of TAIC is 0.5 wt %, and the other steps are consistent with Example 1.
[0074] Embodiment 14
[0075] Add LiPO to the electrolyte 2 F 2 , LiPO 2 F 2 The content of is 0.3wt%, and the other steps are consistent with Example 1.
[0076] Embodiment 15
[0077] Add LiPO to the electrolyte 2 F 2 , LiPO 2 F 2 The content of is 1wt%, and the other steps are consistent with Example 1.
[0078] Example 16
[0079] Add LiPO to the electrolyte 2 F 2 and tris(trimethylsilyl)borate, LiPO 2 F 2 The content of is 0.3wt%, the content of tris(trimethylsilyl)borate is 0.5wt%, and the other steps are consistent with Example 1.
[0080] Embodiment 17
[0081] Tris(trimethylsilyl)borate was added to the electrolyte, the content of tris(trimethylsilyl)borate was 1 wt %, and the other steps were the same as those in Example 1.
[0082] Embodiment 18
[0083] Add LiPO to the electrolyte 2 F 2 and LiBF 4 , LiPO 2 F2 The content of LiBF is 0.3wt%, 4 The content of is 0.3wt%, and the other steps are consistent with Example 1.
[0084] Comparative Example 1
[0085] In the electrolyte, the first solvent is not added, the non-aqueous solvent is EMC, and the other steps are consistent with Example 1.
[0086] Comparative Example 2
[0087] No TAIC was added to the electrolyte, and the other steps were the same as those in Example 1.
[0088] Comparative Example 3
[0089] In the electrolyte, TAIC was not added, but vinyl sulfate was added, and the content of vinyl sulfate was 0.5 wt %. The other steps were consistent with Example 1.
[0090] In the present invention, in Examples 1-18 and Comparative Examples 1-3, different electrolytes were used to prepare lithium ion batteries, and the performance of the lithium ion batteries was tested. The test results are shown in Table 1.
[0091] In one embodiment of the present invention, the test method of the direct current resistance (DCR) test of 50% SOC is as follows: adjust the temperature of the incubator to a constant 25°C, put the lithium-ion battery into the incubator and let it stand for 10 minutes, charge the battery to 4.3V at a constant current of 0.33C, then set the constant voltage to 0.05C, let it stand for 10 minutes, and then discharge it to 2.5V at 0.33C to obtain the theoretical capacity of the battery. Then charge it to 4.3V at a constant current of 0.33C, then set the constant voltage to 0.05C, let it stand for 10 minutes, and then discharge it at 0.33C to adjust the capacity to 50% state of charge (State of Charge, SOC). After standing for 1 hour, record the initial voltage V of the battery. 1 Then the battery is charged at a current of 4C 0 Discharge for 30 seconds and record the battery voltage V after discharge 2 . Calculate the DCR of the battery at 50% SOC using the following formula: DCR (mΩ) = (V 1 -V 2 ) / I 0 .
[0092] In one embodiment of the present invention, the test method for the fast charge capacity retention rate at 25°C is as follows: at 25°C, the lithium-ion battery is charged to 4.3V at different rates (0.33C, 1C, 2C, 3C, 4C) in sequence, and then charged at 4.3V constant voltage until the current is less than 0.05C. After standing for 10 minutes, it is discharged to 2.5V at 0.33C constant current. Among them, each rate is cycled twice in sequence, and the charging capacity of the second cycle at 0.33C rate and the second cycle at 4C rate are recorded as the charging capacity of the lithium-ion battery at 0.33C and 4C. The fast charge capacity retention rate of the large rate 4C is calculated according to the following formula: fast charge capacity retention rate (%) = (4C charging capacity / 0.33C charging capacity) × 100%.
[0093] In one embodiment of the present invention, the test method of the 60°C high-temperature storage capacity retention test is as follows: after the lithium-ion battery is fully charged, it is placed in a constant temperature box at 60°C for storage for 15 days, and after sufficient cooling, it is discharged at a rate of 0.33C to the cut-off voltage, and its capacity is compared with the percentage of the discharge capacity before storage.
[0094] Table 1. Performance of lithium-ion batteries in Examples 1-18 and Comparative Examples 1-3
[0095]
[0096] As shown in Table 1, it can be seen from the comparison of Examples 1-7 that as the content of the first solvent increases, the DCR of the lithium-ion battery gradually decreases, and the fast charge capacity retention rate and high temperature capacity retention first increase and then decrease. This indicates that the mass ratio of the first solvent to the second solvent needs to be controlled within the range of 1:1.83 to 1.25:1, so that the lithium-ion battery can have good electrochemical stability and good kinetic performance.
[0097] Please refer to Table 1. By comparing Examples 1, 8-11 and Comparative Example 1, it can be seen that when different first solvents are selected, the performance of the lithium-ion battery can be improved, but the changes in the DCR, fast charge capacity retention rate and high temperature capacity retention rate of the lithium-ion battery are different. When different second solvents are selected, the performance of the lithium-ion battery can be improved, but the changes in the DCR, fast charge capacity retention rate and high temperature capacity retention rate of the lithium-ion battery are different. Therefore, different first solvents and second solvents can be selected according to usage needs.
[0098] Please refer to Table 1. By comparing Examples 1 and 12-13, it can be seen that as the content of the first additive increases, the DCR of the lithium-ion battery increases, the fast charge capacity retention increases first and then decreases, and the high temperature capacity retention decreases first and then increases, indicating that if the content of the first additive is too low, the decomposition rate of the salt anions cannot be effectively slowed down, the interface phase is unstable, and the battery cycle performance is affected. If the content of the first additive is too high, the organic content in the interface phase is too high, the impedance increases, and the dynamics of the battery are affected. Therefore, the content of the first additive is controlled to improve the performance of the lithium-ion battery.
[0099] As shown in Table 1, by comparing Examples 1, 14-15, it can be seen that when the second additive is added to the electrolyte and the mass ratio of the first additive to the second additive is within (0.3-1): 1, the fast charging performance and high temperature performance of the lithium-ion battery can be improved. When the mass ratio of the first additive to the second additive exceeds this ratio range, the impedance increases and the fast charging capacity retention rate decreases. This is because the proportion of inorganic components in the interface phase decreases, thereby increasing the impedance of the battery and causing the cycle performance to decline.
[0100] Please refer to Table 1. By comparing Example 1 and Examples 16-18, it can be seen that when the third additive is added, the performance of the lithium-ion battery is further improved, indicating that the third additive can cooperate with the first additive and the second additive to make the interface phase more complete and dense, thereby further improving the performance of the lithium-ion battery.
[0101] The present invention also provides an electronic device, the electronic device includes at least one of the above-mentioned lithium-ion batteries, and the lithium-ion battery is used to provide electrical energy. Among them, the electronic device can be a vehicle, a mobile phone, a portable device, a laptop computer, a ship, a spacecraft, an electric toy and an electric tool, etc. In one embodiment of the present invention, the vehicle is, for example, a new energy vehicle, and the new energy vehicle can be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. Spacecraft include airplanes, rockets, space shuttles and spacecrafts, etc. Electric toys include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys and electric airplane toys, etc. Electric tools include metal cutting electric tools, grinding electric tools, assembly electric tools and railway electric tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers, etc. The electronic device includes the above-mentioned lithium-ion battery, so the advantages of the above-mentioned lithium-ion battery are included, which will not be elaborated here.
[0102] In summary, the present invention proposes a lithium-ion battery electrolyte and its application. The first solvent and the second solvent are used together to make the electrolyte have good electrochemical stability and good kinetic performance at the same time, which can effectively improve the fast charging performance of the battery and improve the cycle life of the lithium-ion battery. By adding the first additive, the reaction rate of the salt anion at the interface can be effectively slowed down, thereby alleviating the problem of excessive local temperature, and the high temperature performance of the lithium-ion battery is further improved. The obtained electrolyte can be applied to high-energy-density lithium-ion batteries, improve the fast charging performance of lithium-ion batteries, improve the cycle performance of lithium-ion batteries, and improve the high temperature performance of batteries.
[0103] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above-mentioned technical features, but should also cover other technical solutions formed by any combination of the above-mentioned technical features or their equivalent features without departing from the inventive concept, such as a technical solution formed by replacing the above-mentioned features with (but not limited to) technical features with similar functions disclosed in this application.
[0104] Except for the technical features described in the specification, the remaining technical features are known technologies to those skilled in the art. In order to highlight the innovative features of the present invention, the remaining technical features will not be described here in detail.
Claims
1. A lithium ion battery electrolyte, characterized in that: At least the following components are included: A non-aqueous solvent, the non-aqueous solvent comprising a first solvent and a second solvent, the first solvent being selected from at least one of perfluorohexanone, decafluoropentane or 2,2-bis(trifluoromethyl)-1,3-dioxolane; lithium salts; and The additives include a first additive including triallyl isocyanurate.
2. The lithium ion battery electrolyte according to claim 1, characterized in that: The content of the first solvent in the electrolyte is 5wt% to 40wt%.
3. The lithium ion battery electrolyte according to claim 1, characterized in that The content of the first additive in the electrolyte is 0.01 wt % to 1 wt %.
4. The lithium ion battery electrolyte according to claim 1, characterized in that: The second solvent is selected from at least one of ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, propylene carbonate or ethylene carbonate.
5. The lithium ion battery electrolyte according to claim 4, characterized in that: The second solvent is selected from ethyl methyl carbonate, and the mass ratio of the first solvent to the second solvent is 1:1.83 to 1.25:
1.
6. The lithium ion battery electrolyte according to claim 1, characterized in that: The lithium salt is selected from at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethylsulfonyl imide), lithium bis(oxalatoborate), lithium difluorobis(oxalatophosphate), lithium difluorooxalatoborate or lithium trifluoromethylsulfonate, and the content of the lithium salt in the electrolyte is 10 wt % to 20 wt %.
7. The lithium ion battery electrolyte according to claim 1, characterized in that: The additive further includes a second additive, the second additive includes lithium difluorophosphate, and the content of the second additive in the electrolyte is 0.05wt% to 2.5wt%.
8. The lithium ion battery electrolyte according to claim 7, characterized in that: The mass ratio of the first additive to the second additive is (0.3-1):
1.
9. The lithium ion battery electrolyte according to claim 1, characterized in that: The additives also include a third additive, which is selected from at least one of tris(trimethylsilyl)borate, tripropynyl phosphate, ethylene sulfite or lithium tetrafluoroborate, and the content of the three additives in the electrolyte is 0.01wt% to 1wt%.
10. A lithium ion battery, characterized in that: include: Positive electrode; A negative electrode plate, the negative electrode plate comprising a negative electrode active material, the negative electrode active material comprising a combination of at least one of soft carbon, hard carbon, artificial graphite, natural graphite, silicon or lithium titanate and a silicon-carbon compound, wherein the content of the silicon-carbon compound in the negative electrode active material is 10wt% to 40wt%; A diaphragm, disposed between the positive electrode sheet and the negative electrode sheet; An electrolyte, wherein the electrolyte is selected from the lithium-ion battery electrolyte according to any one of claims 1 to 9.
Citation Information
Patent Citations
High-voltage electrolyte and lithium ion battery based on same
CN111883839A
Preparation method of in-situ cross-linked polymer electrolyte for high-voltage lithium metal battery
CN115101809A
Electrochemical device and electronic apparatus
CN115832437A
Non-aqueous electrolyte and lithium ion battery containing same
CN116190794A
Electrolyte and lithium-rich manganese-based lithium secondary battery
CN117525584A
Cited By
Lithium ion battery
CN121885732A